Access to justice for children with autism spectrum disorders, 2013-2016 - Henry, Lucy A. (UK Data Service, 2016)
Data collection included two distinct groups of participants. (1) Data collected from 202 typically developing children and 72 autistic children, all in the age range 6-11 years when first seen. (Note that one child on the autism spectrum and one child with typical development had IQ scores below 70.) Data collected from the children included standardised and non-standardised tests for a range of cognitive skills (IQ, language, memory, attention, suggestibility, anxiety) as well as data from the four experimental phases of the research: brief initial interviews; full investigative interviews; identification line-ups; and cross-examinations (note that not all children participated in this final phase). (2) Data collected from three samples of jury eligible adults (ages 18-69, n=260 in total) concerning their credibility ratings of interviews (and some cross-examinations) of selected children with and without autism. Children with a diagnosis of Autism Spectrum Disorder (ASD) display some memory and social communication difficulties that may call into question their abilities as witnesses. The current research examined how children with and without a diagnosis of ASD fared during all the different stages of a criminal investigation, and considered the best ways of eliciting reliable evidence. There were four research questions: 1. How do children with a diagnosis of ASD fare during the different stages of a criminal investigation (initial questioning, an investigative interview, when identifying perpetrators, and during cross-examination) relative to typical children? 2. What can be done to improve the amount of information that children recall, without making them more prone to errors; for example, is the assistance of a Registered Intermediary - a professional communications specialist who assists vulnerable individuals within the criminal justice system - useful? 3. How do the general public – who may be evaluating evidence within a jury - perceive child witnesses with and without a diagnosis of ASD? 4. Can we predict how well children will perform as witnesses? For example, is it the case that children with good language, attention or memory skills, are more likely to provide full and accurate statements.